The role and determinants of women labor force participation for household poverty reduction in Debre Birhan town, North Shewa zone, Ethiopia - Girma Mulugeta (Cogent Economics & Finance, 2021)
Women participation in economic activities plays a critical role in driving economic development throughout the world. This study aims to analyze the role and determinants of women's labor force participation for reducing household poverty in the case of Debre Birhan town. To carry out this, the study used a cross-sectional study design. The data was collected by distributing questionnaires to a total of 291 sample households using multi-stage sampling technique. Logistic regression model was employed to analyze the determinants of women labor force participation by the collected data. The binary logit regression result identified that training, exposed to mass media and access to credit and education status of woman were found to be positive and significantly related to the probability of being participate. Moreover, Logistic regression model was employed in order to analyze the effect of woman labor force participation to household poverty reduction, with the probability of a household being poor as a dependent variable and a set of demographic and socioeconomic variables as the explanatory parameters. Based on this, out of the 291 surveyed household heads, 183(62.89%) of them were found poor. The result of this study confirms that women's participation reduces the household poverty. Therefore, this study recommends that household uses family planning, promotes woman to attend higher education, exposed to mass media, creating public or private daycare centers for child and access to credit for woman. At this juncture both the households and the government should have the joint effort and responsibility to find possible panaceas.
Keywords: 330; Debre birhan town; determinants; labor participation; poverty; Women